Konten Sarkasme, TikTok, dan Remaja - Pradana, Johannes; Savitri Setyo Utami, Lusia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
In general, the language of sarcasm is used to ridicule and even beat the speech partner. Sarcasm language refers to harsh words and contains scathing jokes or satire that can hurt someone's heart. Sarcasm in social media is ridicule or ridicule that is expressed either in writing, photos, or videos. The social media that is widely used by Indonesian people from all walks of life is the TikTok application. One example of sarcasm on TikTok is in the TikTok content of a teenager @ramdani_eka who misused the word